Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.amjmed.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Course of Venous Thromboembolism May Differ According to Cancer Site

Abstract: Significant differences in the clinical profile of venous thromboembolic-related outcomes were observed according to the site of cancer. These findings suggest the development of cancer-specific anticoagulant strategies as an area for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 28 publications
(34 reference statements)
6
48
0
1
Order By: Relevance
“…The clinical course of VTE and response to anticoagulant therapy in terms of balance between fatal VTE and fatal bleeding may differ according to cancer site, which is an interesting area for further research. 35 Finally, our metaanalysis is based on data from selected populations from clinical trials, 36 but causes of death are consistent with those reported in unselected populations in standard practice. 30…”
Section: Discussionsupporting
confidence: 52%
“…The clinical course of VTE and response to anticoagulant therapy in terms of balance between fatal VTE and fatal bleeding may differ according to cancer site, which is an interesting area for further research. 35 Finally, our metaanalysis is based on data from selected populations from clinical trials, 36 but causes of death are consistent with those reported in unselected populations in standard practice. 30…”
Section: Discussionsupporting
confidence: 52%
“…Real‐world observational data have suggested higher rates of VTE as well as major bleeding in unselected patients including those with more comorbid conditions less likely to enter clinical trials . Furthermore, cancer site may widely influence both the risk of VTE and bleeding on anticoagulant . These important questions cannot be addressed by meta‐analyses of RCTs and highlight the importance of longitudinal observational thromboprophylaxis studies that included unselected patients with various malignancy types.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, all these studies have examined the rates of recurrent VTE and bleeding in pooled patient populations with different types of cancer. Since significant differences in the clinical course of VTE have been observed according to the site of cancer [31,32], this approach may have failed to capture these differences.…”
Section: Risk Of Recurrent Vte and Bleeding In Patients With An "Actimentioning
confidence: 99%